An assessment of the effectiveness of training for extension staff in the Limpopo Department of Agriculture - Mashamba, Mpho Abigail (University of Limpopo (Turfloop Campus), 2012)
Agricultural Extension workers could play a key role in fostering sustainable agriculture production as well as economic growth. The training for extension staff is a step towards sustainable development. Agriculture is an important sector in the South African economy. Its existence impacts directly on job creation, rural development, food security, foreign exchange and poverty reduction. Because the agricultural sector is crucial to rural development and contributes significantly to any initiative to alleviate poverty, it is for this reason that there is a great need for strong extension and advisory services led by governmental operations in partnership with relevant role-players. The study therefore makes use of qualitative data to determine the level and frequency of achievements, challenges, and demographic information of extension officers. Data collection instruments, such as interviews and group discussion, are used to measure the outcomes of the extension training. The results of this study will inform the Department of Agriculture on the achievements, challenges and resolutions into enhancing effectiveness of training for extension staff. The major conclusions and recommendations include: A majority possess national diplomas. In terms of the job requirement, a person must possess a BSc degree in agriculture. It is recommended that bursary must be awarded to extension officers with diplomas so that they upgrade their qualification to a BSc degree. A majority of the extension officers received on the job training, for example, in customer care, HR practices, participatory extension approach and basic computer literacy. It is recommended that training should be accelerated in participatory extension approach, and customer because of the imperative to transmit agricultural skills and knowledge to the farmers in endeavour to promote sustainable agriculture and rural development. According to the study, the training provided to most extension officers was outdated because it was not applicable to current challenges. It is recommended that a study should be undertaken on the situational analysis of the challenges being experienced by the farmers. The study also found out that the infrastructure such as office accommodation, poor technology; insufficient funds disabled the extension officers to transfer the skills to the farmers. It is recommended that there should be sufficient resources to address these challenges.
Thesis (M.Dev.) --University of Limpopo, 2012
Keywords: Agricultural extension staff; 630.715; Continuing education; Rural extension; Agricultural extension work